Rectifying effect from prototype DNA-Schottky diode / Chan Zhijian - Chan , Zhijian (2017)
In recent years, deoxyribonucleic acid (DNA) has been a targeted field of research due to its various properties and easy availability. Research findings have highlighted the semiconducting ability of the DNA molecule. However, proper understanding of its functionalities and properties, especially in the form of DNA film is inadequate. In this research, DNA thin films were prepared using the Langmuir-Blodgett (LB) method in the development of an Indium-Tin Oxide (ITO)/DNA/Aluminium (Al) Schottky diode. The thin film was analysed using structural and imaging techniques such as Atomic Force Microscopy (AFM) and Field Emission Scanning Electron Microscopy (FESEM). The film produced demonstrated a uniformly repeating pattern. The prototype sensor was then subjected to electrical characterisation involving acquisition of current-voltage (I-V) graphs, which suggested rectifying behaviour of the DNA molecule. Further studies of electrical behaviour revealed that electric field alignment improves electrical conductivity with a potential barrier of 0.796 eV for non-aligned films and 0.780 eV for aligned films. Significant improvements on measured ideality factor and series resistance post electric field alignment have also been observed. The results obtained suggest an exciting opportunity to achieve functional semiconductor properties for future research on fabrication of efficient and low-cost hybrid electronic devices based on DNA.